2022
DOI: 10.3390/ijms232012266
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone-Acridine Hybrid Suppresses Melanoma Cell Progression via G2/M Cell Cycle Arrest, DNA Damage, Apoptosis, and Modulation of MAP Kinases Activity

Abstract: This study was focused on investigating the antiproliferative effects of chalcone hybrids in melanoma cancer cells. Among seven chalcone hybrids, the chalcone-acridine hybrid 1C was the most potent and was selected for further antiproliferative mechanism studies. This in vitro study revealed the potent antiproliferative effect of 1C via cell cycle arrest and apoptosis induction. Cell cycle arrest at the G2/M phase was associated with modulation of expression or phosphorylation of specific cell cycle-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Compound 12 has also shown a more important effect than the acridine chalcone 1C, reported by Gazdova et al [38], on the proliferation of MCF-10A melanoma cell line (IC 50 = 36.54 µM). Yet, the acridine chalcone 1C displayed a more important effect on other melanoma cell lines, like A2058 (IC 50 = 7.96 µM) or BLM (IC 50 = 17.93 µM), showing that its effect depends on the tested cell line.…”
Section: Antimelanoma Activitiesmentioning
confidence: 72%
“…Compound 12 has also shown a more important effect than the acridine chalcone 1C, reported by Gazdova et al [38], on the proliferation of MCF-10A melanoma cell line (IC 50 = 36.54 µM). Yet, the acridine chalcone 1C displayed a more important effect on other melanoma cell lines, like A2058 (IC 50 = 7.96 µM) or BLM (IC 50 = 17.93 µM), showing that its effect depends on the tested cell line.…”
Section: Antimelanoma Activitiesmentioning
confidence: 72%
“…Numerous studies have reported that chalcones induce cell cycle arrest in the G2/M phase. For example, certain chalcone–acridine hybrids and quinoline–chalcone hybrids have shown efficacy in inhibiting melanoma cell progression by inducing G2/M cell cycle arrest, DNA damage, apoptosis and the modulation of MAP kinase activity [ 261 ]. In addition, treatment with 2′,4′-dihydroxychalcone has led to an accumulation of G2/M phase in human gastric carcinoma cells [ 262 ].…”
Section: Natural Michael Acceptors In Cancer Prevention and Treatmentmentioning
confidence: 99%
“…Such new molecules are either of natural origin or synthetically created. Examples can be chalcones and pyrrolidines, which are known for inducing apoptosis in tumour cells [39,40]. Due to the disadvantages of 2D cultures, it was necessary to develop strategies to better understand the processes taking place in tumours, such as 3D cultures.…”
Section: Two-dimensional Culture Pros and Consmentioning
confidence: 99%